Preparation And Properties Of Polypropylene/Waste Tyre Dust/Short Glass Fibre (Pp/Wtd/Sgf) Composites - Zainal, Zuriati (2017)
Polypropylene/ waste tyre dust/ short glass fibre (pp/wtd/sgf) composites were meltmixed in an internal mixer at 180 °c and 50 rpm rotor speed. Four series of composites with various compositions were prepared using wtd of 250-500 pm and at different 5, 10, 15 and 20 php sgf loading. Characterization was done to determine the properties of the composites and thus to study the effects of sgf loading, the incorporation of silane coupling agent, y-aminopropyltrimethoxysilane (y-aps) and dynamic vulcanization (dv), the hybridization of sgf with carbon black (cb) and silica on processing characteristics, mechanical properties, morphology, swelling resistance and thermal properties of the composites. The incorporation of sgf at various loadings exhibited increased equilibrium processing torque, young’s modulus, tensile strength and thermal stability while elongation at break (eb) and swelling resistance decreased as the sgf loading increased in pp/wtd/sgf composites. Poor interfacial adhesion between sgf and pp/wtd matrix was depicted in the sem analysis. In the meantime, the addition of y-aps, and dv revealed the increased of equilibrium torque, tensile properties except eb and swelling resistance of pp/wtd/sgf composites.